Trade in services in South Asia : opportunities and risks of liberalization - Kelegama, Saman; Kelegama, Saman (Los Angeles Colombo Sri Lanka SAGE Friedrich-Ebert-Stiftung IPS, 2009)
Revised version of papers presented at the International Conference on "Trade in Services in South Asia : Opportunities and Risks in Liberalization", held at Colombo during 4-5 April 2007.
"Revised papers that were presented at an International Conference on 'Trade in services in South Asia: opportunities and risks in liberalization' organized by the Institute of Policy Studies of Sri Lanka (IPS) and Friedrich-Ebert-Stiftung (FES), Colombo, during April 4-5, 2007"--Acknowledgements.
Keywords: Free trade -- South Asia -- Congresses